2020
DOI: 10.1021/acs.iecr.0c03818
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boron Nitride Addition on Ablation Characteristics of Carbon Fiber Reinforced Resorcinol Formaldehyde Composites

Abstract: The effect of boron nitride (BN) addition in carbon fiber reinforced resorcinol formaldehyde (C-RF) composites was explored in this study. Composites are altered with various weight proportions of boron nitride to make boron nitride incorporated carbon fiber reinforced resorcinol formaldehyde (BN-C-RF) composites. The ablation resistance of BN-C-RF composites was observed to be the maximum when the BN to RF ratio is 0.05:1. The thermomechanical properties of composites were studied. The thermally ablated compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 72 publications
(112 reference statements)
0
8
0
Order By: Relevance
“…The weight loss below 300 °C is not mainly owing to the pyrolysis of phenolics but the release of water as well as the unreacted monomers. 2,15,43 The second step of 300−800 °C, in which significant weight changes are observed in the TG curves, is ascribed to the pyrolysis of phenolics. With the gradual collapse of the polymer network and deformation of the polyaromatic structure, many kinds of volatiles including CO, CO 2 , CH 4 , C 2 H 2 , C 2 H 6 , etc., are released out, resulting in the gradual decrease in weight.…”
Section: Resultsmentioning
confidence: 99%
“…The weight loss below 300 °C is not mainly owing to the pyrolysis of phenolics but the release of water as well as the unreacted monomers. 2,15,43 The second step of 300−800 °C, in which significant weight changes are observed in the TG curves, is ascribed to the pyrolysis of phenolics. With the gradual collapse of the polymer network and deformation of the polyaromatic structure, many kinds of volatiles including CO, CO 2 , CH 4 , C 2 H 2 , C 2 H 6 , etc., are released out, resulting in the gradual decrease in weight.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the crystal structures and crystallite size of the species were determined by d 002 and La in Table 2, according to the Scherrer and Bragg equations. 24,25 The results showed that the d 002 of POSSPBR decreased from 0.4226 to 0.3419 nm, lower than that of BPR, as the temperature increased. And the La of POSSBPR increased to 3.18 nm under 1600 C heat treatment.…”
Section: High-temperature Thermochemical Structural Transformation Of...mentioning
confidence: 95%
“…The structure of the carbon and the ceramic structure of the resin after ablation are crucial to its anti-ablation property. 24 To determine the changes of carbon microcrystalline and ceramic structure transformation of carbonized BPR and POSSBPR at different temperatures, XRD, Raman spectroscopy, and SEM were performed in Figure 4.…”
Section: High-temperature Thermochemical Structural Transformation Of...mentioning
confidence: 99%
“…Customarily, exfoliation refers to the technique involving the expansion of layered materials employing extraneous factors, i.e., physical or chemical forces to diminish the interlayered noncovalent interactions, eventually segregating them into monolayered sheets . The majority of the layered materials , including graphene, molybdenum disulfide (MoS 2 ), and hexagonal boron nitride (hBN) , are bound by feeble secondary forces along the (001) plane causing facile detachment of the layers via chemical or mechanical methodologies by surmounting the secondary forces. Exfoliation of bulk materials into distinct layered sheets of 10 –9 m thickness imparts a diverse spectrum of material characteristics, such as substantial augmentation in the surface area to volume ratio consequently yielding enhanced catalytic activity and reactivity of these materials that cannot be achieved in its bulk state.…”
Section: Introductionmentioning
confidence: 99%